On the identity of Oberea acuta Gressitt, 1951, O. bisbipunctata Pic, 1916, O. notata Pic, 1936 and O. shimomurai Kurihara & N. Ohbayashi, 2007 (Coleoptera, Cerambycidae, Lamiinae) with a new synonym - Li, Zhu; Cuccodoro, Giulio; Chen, Li (Zootaxa, 2021)
Oberea acuta Gressitt, 1951 is redescribed, the diagnosis of O. notata Pic, 1936 and O. bisbipunctata Pic, 1916 were provided based on examination of type material and additional specimens. Illustrations of habitus and genitalia are provided, and a key to separate these three species is presented. Their distribution is critically examined, notably that of O. bisbipunctata, whose previous records in China are invalidated. Oberea shimomurai Kurihara & N. Ohbayashi, 2007 is considered a junior synonym of Oberea notata Pic, 1936.